Characterization of alpha-neurotoxin and phospholipase A2 activities from Micrurus venoms. Determination of the amino acid sequence and receptor-binding ability of the major alpha-neurotoxin from Micrurus nigrocinctus nigrocinctus - Bougis, Pierre Edouard (1996)
New World elapids are coral snakes that belong to the genus Micrurus, and for which the venom biochemistry is mostly unknown. Analysis has been difficult because the coral snakes produce small quantities of venom. Clinical observations following bites show mainly neurotoxic effects. Experimentally, cardiotoxic, haemolytic and myotoxic activities are also reported. An experimental approach, using reverse-phase high-performance liquid chromatography and specific assays for alpha-neurotoxin and phospholipase A2 activities, was conducted on milligram quantities of venoms from three Micrurus species from Costa Rica; M. nigrocinctus nigrocinctus, M. alleni yatesi and M. multifasciatus. Neurotoxicity was determined by competition binding experiments with the Torpedo marmorata acetylcholine receptor. Phospholipase A2 activity was measured by fluorimetry using a pyrene lipid substrate. In this way, we purified and characterized seven alpha-neurotoxins, five phospholipases A2 and four toxin homologs. The amino acid sequence of the major alpha-neurotoxin from M. nigrocinctus nigrocinctus venom was fully determined and compared to Old Word representatives. Distance matrix data were generated to set up phylogeny relationships among elapid short-chain alpha-neurotoxins, which proved to be in accordance with the taxonomic classification and geographical distribution of snake species.